CAPABILITY AND SWIMMING ENDURANCE OF TAPAH FISH (Wallago leeri) IN ROTATED TANK (FLUME TANK) - Ghifari, Dwika; Nofrizal, Nofrizal; Jhonnerie, Romie (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Tapah fish (Wallago leeri) is a type of freshwater fish with high economic value. Swimming speed and endurance (Wallago leeri) observed in swimming chanel flume tank. The purpose of this study was to test the endurance and swimming speed of tapah fish. This research was conducted on 1-15 November 2018 in the Laboratory of Fishing Gear and Material of the Faculty of Fisheries and Marine, University of Riau. The method used in this study was an experiment in which of testing is done directly with the number of samples used were 20 fish with an average body length of 27.2 cm and was obtained a standard deviation of body length (+ 2.22 cm). Based on the testing results obtained sustained tapah fish swimming speed sustained <0.42 TL / sec, maximum sustained 0.42 TL / sec (11.50 cm / sec), prolonged ranges from 0.42-2.23 TL / sec, burst swimming speed 2.23 TL / sec. The relationship between swimming speed and endurance of tapah fish swimming is negative correlation with the value (R2 = 0.89) which means that the endurance of fish swimming decreases if it is in a situation of high swimming speed and the ability of fish swimming is drastically reduced. Based on the results of the test it can be recommended for the cultivation floating cages the tapah fish can use the waters with currents of 0.42 TL / sec (11.50 cm / sec) which is the daily swimming speed of the tapah fish. Key word : Swimming Speed, Ability and Endurance,Tapah Fish